2013
DOI: 10.1128/jb.02277-12
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase/Phosphatase Function Correlates with Gliding Motility in Mycoplasma pneumoniae

Abstract: Mycoplasma pneumoniae exhibits a novel form of gliding motility that is mediated by the terminal organelle, a differentiated polar structure. Given that genes known to be involved in gliding in other organisms are absent in M. pneumoniae, random transposon mutagenesis was employed to generate mutants with gliding-deficient phenotypes. Transposon insertions in the only annotated Ser/Thr protein kinase gene (prkC; MPN248) and its cognate phosphatase gene (prpC; MPN247) in M. pneumoniae resulted in significant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…wild-type levels in both mutants (Page and Krause, 2013), consistent with identification of all core substructures in tomograms here. As likely regulatory rather than structural proteins, both may be present in low abundance, and attempts at their detection using antibodies raised against multiple antigenic peptides for each were unsuccessful (Page and Krause, 2013).…”
Section: Resultssupporting
confidence: 88%
“…wild-type levels in both mutants (Page and Krause, 2013), consistent with identification of all core substructures in tomograms here. As likely regulatory rather than structural proteins, both may be present in low abundance, and attempts at their detection using antibodies raised against multiple antigenic peptides for each were unsuccessful (Page and Krause, 2013).…”
Section: Resultssupporting
confidence: 88%
“…Electron microscopy has demonstrated that the adhesion of a M. pneumoniae variant is concentrated in the adherend in the following order: HMW1, HMW3, Pl, P30, P90, P40 and P65, which indicates that these proteins have formed an interrelated adhesion network (12). Specifically, HMW1, HMW2 and HMW3 function as stable adherends and allow other adhesions to locate onto the adherend, and, they are involved in the adhesion onto the respiratory tract epithelia (13). As reported, the M. pneumoniae mutant strains, HMW1 and HMW2, can prevent the P1 protein from correctly locating onto the apical structure, which leads to irregular cell morphology, loss of toxicity and sliding ability, and loss of adhering function (14).…”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…Mycoplasmas were grown at 37°C in SP-4 medium (30) until the phenol red pH indicator turned orange. Antibiotic selection was included for the prpC mutant (25). For radiolabeling studies, mycoplasmas were cultured in the presence of 100 Ci [methyl- 3 H]thymidine (6.7 Ci/mmol; PerkinElmer), harvested and collected by centrifugation, and washed 3 times in fresh SP-4 medium as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type M. pneumoniae (strain M129, 17th broth passage) (15); P30 mutants II-3, II-7, and II-3R (7,24); the P200 mutant (22); and the prpC mutant (25) were included in the current study. P30 is a terminal organelle protein required for adherence to host cells and gliding motility (5,6,26).…”
Section: Methodsmentioning
confidence: 99%